Association Between Physical Activity Level and Training Volume in Adolescent Athletes - Sebastian Sitko; Alejandro Legaz-Arrese; Joaquín Reverter-Masia; Diego Moliner-Urdiales; Vicenç Hernández-González; Saül Aixa-Requena; Enric Conesa-Milian; Carmen Mayolas-Pi (Sports)
Organized sports are assumed to boost overall physical activity, but evidence suggests structured training does not always increase general activity outside formal sessions. This study explores the link between physical activity levels and weekly training hours in adolescent athletes across sports and competition levels. A total of 10,196 participants aged 11 to 19 were included in the analyses. Participants were classified into seven groups: inactive, somewhat active, non-competitive athletes, and athletes competing at the local, regional, national, or international level. They completed the Spanish version of the Physical Activity Questionnaire and answered questions regarding their performance level, training volume, and socioeconomic status. Girls exhibited lower physical activity levels than boys, even at higher competition levels where both sexes had comparable training hours. Competitive athletes reported the highest physical activity levels. In competitive athletes, physical activity levels decreased with age despite a substantial increase in weekly training hours. They were similar across athletes competing in different sports and at different levels, despite significant differences in training hours. Many athletes, including those at the national and international levels, displayed low physical activity levels, and no clear relationship was found between physical activity level and weekly training hours. The current study provides valuable insights into adolescent physical activity patterns by sex, age, sport, and competition level. Girls showed lower physical activity than boys, even with similar training hours. Physical activity levels declined with age despite increasing training volumes, and no strong association was observed between physical activity and weekly training hours. These results reveal a discrepancy between structured training and overall activity levels, challenging assumptions about the impact of sports participation on daily physical activity.